2011
DOI: 10.1177/0194599811411534
|View full text |Cite
|
Sign up to set email alerts
|

Association between Cerebrospinal Fluid Leak and Meningitis after Skull Base Surgery

Abstract: Postoperative CSF leak significantly increases the risk of meningitis. Most cases of meningitis after skull base operation are probably associated with lumbar drainage infection or from an obscure leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 38 publications
1
47
0
3
Order By: Relevance
“…Horowitz et al showed that postoperative CSF leak significantly increases the risk of meningitis. 17 Hence, a decision to breach it intentionally has to be weighed carefully. In our own results, all the leaks occurred only when the dura was breached.…”
Section: Discussionmentioning
confidence: 99%
“…Horowitz et al showed that postoperative CSF leak significantly increases the risk of meningitis. 17 Hence, a decision to breach it intentionally has to be weighed carefully. In our own results, all the leaks occurred only when the dura was breached.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] The most commonly correlated finding was an intra-or postoperative CSF leak, which may result in the development of meningitis through failure of a tight closure of the cranial diaphragm, catheter infection of the lumbar drain, ascending infection from an obscure leak, or ascending infections from the contaminated paranasal sinuses via the skull base defect during or after surgery. 11,14 Lai et al 7 systematically studied the incidence of meningitis after endoscopic endonasal skull base surgery from 1950 to 1980 and reported a rate of 1.8%. This number was strongly correlated with a CSF leak because meningitis occurred in 13% of those who reported a CSF leak (35/269) and only 0.1% without a CSF leak (1/1736).…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative meningitis is uncommon and seems to be most commonly associated with postoperative cerebrospinal fluid (CSF) leak. [7][8][9][10][11][12][13] This rarity of reported meningitis is thought to be due to the high vascularity of the head and neck, and infrequency of dural disruption during dissection, so the presence of CSF leak may be worth examining as an independent risk factor. However, with advancing techniques and experience, transdural surgery is becoming more commonplace, and, yet, meningitis is still a rare complication.…”
mentioning
confidence: 99%
“…Displacement of the flap may lead to severe complications, such as CSF leak, pneumocephalus, and meningitis, which may require a second operation. 18 Flap migration and reconstruction breakdown may occur for several reasons: 1) the support is not anatomically shaped as in the case of a balloon catheter, leading to unequal pressure vectors over the flap and to its traction; 2) malpositioning of the support that is placed blindly and not under endoscopic guidance; and 3) migration or change in the shape of the support during the early postoperative period, such as in the case of leaking Foley catheters. The TSB precisely addresses these drawbacks of conventional supporting methods.…”
Section: Discussionmentioning
confidence: 99%